DNA origami-designed 3D phononic crystals - Park Sung Hun; Park Haedong; Nam Jwa-Min; Ke Yonggang; Liedl Tim; Tian Ye; Lee Seungwoo (Nanophotonics)
Moulding the flow of phononic waves in three-dimensional (3D) space plays a critical role in controlling the sound and thermal properties of matter. To this end, 3D phononic crystals (PnCs) have been considered the gold standard because their complete phononic bandgap (PnBG) enables omnidirectional inhibition of phononic wave propagation. Nevertheless, achieving a complete PnBG in the high-frequency regime is still challenging, as attaining the correspondingly demanded mesoscale 3D crystals consisting of continuous frame networks with conventional fabrications is difficult. Here, we report that a DNA origami-designed-3D crystal can serve as a hypersonic 3D PnC exhibiting the widest complete PnBG. DNA origami crystallization can unprecedentedly provide 3D crystals such that continuous frame 3D crystals at the mesoscale are realizable. Furthermore, their lattice symmetry can be molecularly programmed to be at the highest level in a hierarchy of symmetry groups and numbers, which can facilitate the widening of the PnBG. More importantly, conformal silicification can render DNA origami-3D crystals rigid. Overall, we predict that the widest hypersonic PnBG can be achieved with DNA origami-designed 3D crystals with optimal lattice geometry and silica fraction; our work can provide a blueprint for the design and fabrication of mesoscale 3D PnCs with a champion PnBG.